(3GdJMdjd GdeGdj ddbhGFe GdeGdjI hGdEaUGM GdeMGSHj (B/s - (3GdQGhj, NGdO hgjHs; (3SYGOI, jhSa s ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2000)
(3JLO aj gPG GdcJGH (B: (3GdJMdjd GdeGdj ,GdbhGFe GdeGdjI , JMdjd GdJYGOd ,GdJNWjW GdeGdj hGdehGRfGJ GdJbOjQjI ,fXQI gjcd QCS GdeGd Jbje GdeTQhYGJ GdESJKeGQjI ,CgejI GdEaUGM GdeMGSHj aj GdJMdjd GdeGdj , GdeNRhf GdSdYj ,SjGSI QCS GdeGd (B.s
Keywords: (3GdEaUGM GdeMGSHjs; (3GdbhGFe GdeGdjIs; (3GdeMGSHI GdeGdjIs